LABOUR MIGRATION FROM UKRAINE: ECONOMIC AND LEGAL WAYS OF COUNTERING - O. M. Yaroshenko; O. H. Sereda; G. P. Sereda; O. A. Yakovlyev (Фінансово-кредитна діяльність: проблеми теорії та практики, 2021)
The main reasons of labour migration from Ukraine are analysed. It is emphasized that this process becomes a sign of danger for the socio and economic development of Ukraine. The refusal of citizens to work in Ukraine creates a threat to the formation of funds of the Pension Fund of Ukraine, and today the state doesn’t receive the revenues to the budgets, which are formed by the payment of personal income tax. It is emphasized that Ukraine should use the foreign experience and international standards of creation of proper working conditions for workers on the way to counter the labour migration. Such conditions include not only working conditions where occupational safety and hygiene is important, but also remuneration conditions, where fair remuneration must be calculated in the context of purchasing power, which effectively determines the access of workers and their families to social benefits. It is emphasized separately that hired labour has at least 3 interrelated goals. The first one is intended to create gross domestic product in the state and money circulation through trade in goods, works and services. The second one is aimed at physically restoring the working capacity of the worker and ensuring the vital needs of non-working members of the employee's family. The third one is aimed at restoring, stabilizing and developing the mental and social well-being of the employee and his or her family. The research proposes: a) to review, at the national level, the minimum living wage; b) normatively determine the coefficients of wage differentiation not only by the inter-qualification ratio but also by sectoral activities to take into account the professional needs of workers of different professions. The sectoral wage differentiation coefficient is to be paid by the employer at the expense of its wages and salaries. The actual costs of remuneration for work, taking into account the sectoral coefficient of wage differentiation, should be fixed in collective agreements and collective contracts. The primary level of counteraction to labour migration from Ukraine should be enterprises, institutions, organizations.